Idas e vindas ao Passo da Guanxuma: a relação entre espaço ficcional e memória na obra de Caio Fernando Abreu - Cantarelli, Ana Paula (2010)
In 1984, Caio Fernando Abreu created the fictional city of Passo da Guanxuma. Characterizing it as a country town, through the years, this space has assumed a very peculiar signification in the works of this author, as well as a singular location, being situated aside real cities. In this study, we propose ourselves to list the allusions to this place found through the work of Abreu, relating them and comparing them, at the same time that we try to establish a dialogue among characters, actions and space and time references related to it, composing a great open and fractionated novel, in which the analyzed texts present themselves as pieces, as fragments. To reach our goal, we divide this work in three parts. In the first part, we present the biography of the studied author and the analysis of the works that have references to the fictional city studied. In the second, we discuss some aspects of literature in the contemporaneity and do some approaches with Abreu s works, highlighting the reader s role. We also present some considerations about the displacement feeling of characters that migrated from Passo to the great metropolis, relating them with the foreigners sign. In the third, we discuss the globalizing process, the attempt of homogenization that reigns in the metropolis all around the world generating conflicts between the propositions of a universalization (act of turning something universal) and the resistance of the regional cultures, the constant changes in the panorama of big cities and, consequently, in the individuals that inhabit them. We also discuss impossibility of return, although the characters are willing for it, because that individual that have left became other in the same way that the city left behind have also changed, what turns Passo da Guanxuma an even more particular space.